ANALISIS KEAMANAN WIRELESS LOCAL AREA NETWORK (WLAN) TERHADAP SERANGAN BRUTE FORCE DENGAN METODE PENETRATION TESTING (Studi kasus:RS H.LMANAMBAI ABDULKADIR) - Yudi Mulyanto; Herfandi Herfandi; Randi Candra Kirana (Jurnal Informatika Teknologi dan Sains, 2022)
Information and communication at this time absolutely become a basic need that must be met. Even for some people, they need information whenever and wherever they are. And the technology that can fulfill this need is wireless technology. In an interview with Mr. yudi alfiandi as the Information Technology unit. Whereas R S H.L Manambai Abdulkadir often experienced disturbances such as flooding and illegal access. Therefore R S H.L Manambai Abdulkadir needs a network security system analysis in order to ensure that R S H.L Manambai Abdulkadir is good in terms of network security systems, especially wireless networks. Therefore, a standard tool is needed in analysis using the Penetration Testing method. The results of the tests that have been carried out, that access point 1 has a password that is very easy to guess and vulnerable to attacks, so it needs better handling and uses a passphrase.